Cross-linguistic Influences in L2 and L3 Oral Production - Letica, Stela; Mardešić, Sandra (2007)
Most definitions of cross-linguistic influence imply transferability of both native and non-native language knowledge in non-native language production, but current language transfer theories primarily focus on interaction of native and non-native systems (DeAngelis & Selinker, 2001). In our study we were, however, interested in transfer between non-native languages in non-native production. Our aim was to identify cross-linguistic influences in oral production of Croatian L1 speakers of Engish as L2 and Italian as L3. The starting hypothesis was that frequency and direction of cross-linguistic influences between L2 and L3 depend primarily on exposure to the two languages. The sample included 20 participants, university students majoring in English and Italian. Length of study in case of English ranged from 12 to 20 years, while for Italian the length varied between 4 and 12 years, the average lengths being around 14 years and 7 years respectively. Data was collected on participants' language learning history, level of proficiency, exposure to both languages and perceived language distance among L1, L2, and L3. In order to collect language corpus for analysis, we asked participants to perform a picture description task in L2 and L3, as well as, a short oral translation from L1 to L3. The initial hypothesis was confirmed by the findings. The study, however, also brought to the foreground effects of perceived typological distance and proficiency levels. Cross-lingusitic influence was more frequently detected in the non-native language which participants were less proficient in. Even though the three languages included in the study are typologically different, our data shows that the language exerting the highest influence on current oral production was the one that was perceived by participants as typologically closer.
Projekt MZOS
Projekt MZOS
ENG